2013
DOI: 10.1136/emermed-2012-201782
|View full text |Cite
|
Sign up to set email alerts
|

Manchester triage system version II and resource utilisation in the emergency department

Abstract: Emergency department (ED) triage systems aim to direct the best clinical assistance to those who are in the greatest urgency and guarantee that resources are efficiently applied. The study's purpose was to determine whether the Manchester Triage System (MTS) second version is a useful instrument for determining the risk of hospital admission, intrahospital death and resource utilisation in ED and to compare it with the MTS first version. This was a prospective study of patients that attended the ED at a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
3
22

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 8 publications
3
40
3
22
Order By: Relevance
“…This result is similar to studies carried out in Brazil (13) and in Portugal. (14) In Brazil, the mean age of the population was lower (32 years) than in Portugal (53 years). A study conducted in Brazil found that the mean age was also 32 years.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to studies carried out in Brazil (13) and in Portugal. (14) In Brazil, the mean age of the population was lower (32 years) than in Portugal (53 years). A study conducted in Brazil found that the mean age was also 32 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the pediatrics and European context, the classification of patients in standard categories ranged from 34.6% (13) to 45.3% (14) to 52% (15) . In this scenario (15) , even adding patients from category white to those with lower priority, the proportion remained lower than that found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…O contexto internacional é semelhante, sendo apontada uma taxa de utilização inadequada dos SU entre 20% e 40% (Carret, Fassa, & Domingues, 2009). De salientar a elevada variabilidade da taxa de recorrências inadequadas ao SU devido à falta de consenso sobre os critérios a considerar (Santos, Freitas, & Martins, 2014). Face ao exposto este estudo tem como objetivo geral avaliar os determinantes do acesso ao serviço de urgência por utentes não urgentes.…”
Section: Introductionunclassified